“We’re Going to Start Healing”: Perceptions of Sexual Violence on a Rural Indian Reservation in the Northern Great Plains - Ling, Stephanie Lim Mei (Journal of interpersonal violence, 2025)
Indigenous people experience disproportionally higher rates of sexual violence, but we know little about how to prevent sexual violence among this population. The purpose of this study was to understand the perspectives (e.g., causes, prevention) of sexual violence among an Indigenous community residing on a large rural Indian Reservation in the Northern Great Plains. The study conducted seven focus groups with adults, high school students, and middle school students, and a thematic analysis approach was used to assess the gestalt of the data. Three primary themes emerged from the data: (a) causes of sexual violence, (b) characteristics and contexts of sexual violence, and (c) prevention of sexual violence. Specifically, Indigenous relatives desired sexual violence education; however, there was agreement that there is a lack of programming or education from schools and community organizations. Notably, adults focused on how colonization affected the attitudes and behaviors related to sexual violence and the importance of empowering youth. Adolescent boys believed that the general acceptance of physical violence and bullying in their community led to a culture of ambivalence and distrust of sexual assault disclosures. Adolescent girls referenced how gender and social norms that subjugate women/girls have led to rape myth acceptance and victim-blaming. Findings highlight the need for empowerment-based, culturally grounded, gender transformative prevention programs to address the social biases and gender norms that contribute to sexual violence while promoting cultural strengths and community among youth. This research has important implications for informing sexual violence prevention programming across Indian country.